A splicing factor switch controls hematopoietic lineage specification of pluripotent stem cells. (15th December 2020) - Li, Yapu; Wang, Ding; Wang, Hongtao; Huang, Xin; Wen, Yuqi; Wang, BingRui; Xu, Changlu; Gao, Jie; Liu, Jinhua; Tong, Jingyuan; Wang, Mengge; Su, Pei; et al.
Abstract: Alternative splicing (AS) leads to transcriptome diversity in eukaryotic cells and is one of the key regulators driving cellular differentiation. Although AS is of crucial importance for normal hematopoiesis and hematopoietic malignancies, its role in early hematopoietic development is still largely unknown. Here, by using high‐throughput transcriptomic analyses, we show that pervasive and dynamic AS takes place during hematopoietic development of human pluripotent stem cells (hPSCs). We identify a splicing factor switch that occurs during the differentiation of mesodermal cells to endothelial progenitor cells (EPCs). Perturbation of this switch selectively impairs the emergence of EPCs and hemogenic endothelial progenitor cells (HEPs). Mechanistically, an EPC‐induced alternative spliced isoform of NUMB dictates EPC specification by controlling NOTCH signaling. Furthermore, we demonstrate that the splicing factor SRSF2 regulates splicing of the EPC‐induced NUMB isoform, and the SRSF2‐NUMB‐NOTCH splicing axis regulates EPC generation. The identification of this splicing factor switch provides a new molecular mechanism to control cell fate and lineage specification. Synopsis: Alternative splicing leads to transcriptome diversity and drives cellular differentiation. During hematopoietic stem cell differentiation, a splicing factor switch reshapes the transcriptome, thereby instructing the generation of endothelial progenitors. A specific splicing factor switch occurs during hematopoietic differentiation of mesodermal cells to endothelial progenitors. Generation of endothelial progenitor cells is impaired upon splicing inhibition. Specific splicing events in the SRSF2‐NUMB‐Notch axis regulate the specification of endothelial progenitor cells. Abstract : Alternative splicing leads to transcriptome diversity and drives cellular differentiation. During hematopoietic stem cell differentiation, a splicing factor switch reshapes the transcriptome, thereby instructing the generation of endothelial progenitors.